Edukasi dan Simulasi Mitigasi Bencana untuk Siswa SMPN 1 Kejuruan Muda - Basri, Teuku Hasan; Ilyas, Ilyas; Akob, Bachtiar; Nuraini, Nuraini (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2025)
This study aims to enhance students’ understanding and preparedness for potential disasters through a disaster mitigation education and simulation program at SMPN 1 Kejuruan Muda. This area is prone to natural disasters such as floods, earthquakes, and fires, making it necessary to implement systematic preventive approaches from an early age. The method used is a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. The education program was delivered through interactive counseling sessions and educational visual media, while the simulation was conducted in the form of emergency evacuation drills involving the entire school community. The results of the study show a significant increase in students’ understanding of types of disasters, self-rescue procedures, and the importance of cooperation in emergency situations. Moreover, students showed a positive and enthusiastic response to the simulation activities, reinforcing the effectiveness of experience-based learning. Teachers and school staff also actively participated in the program, creating an environment that supports the development of a disaster-aware culture. In conclusion, disaster mitigation education and simulation are effective strategies in fostering students’ alertness and responsiveness to disaster threats. The study recommends integrating disaster education into the school curriculum and conducting regular training sessions as part of strengthening the school’s capacity for disaster resilience.